Avaliando uma proposta de Ensino de Espanhol por meio de discriminações condicionais - Llausas, Rosana Valiñas (2014)
The compulsory teaching of Spanish language was formalized by Law 11.161, enacted in 2005. Considering that teaching of Spanish language is on recent deployment, there is not enough knowledge about how such education is being taught, what the results were and what the best teaching methods. In this context, it becomes important to develop studies that focus on the teaching of the Spanish language in order to produce scientific knowledge that can support the decisions taken by the teacher. It is considered that the Behavior Analysis, based on the model of stimulus equivalence, can contribute with valuable suggestions. Such theoretical and methodological basis has been supporting the development of promising proposals in different areas, as in Portuguese, in the teaching of reading and writing; in Mathematics, teaching numbers and fractions; in Arts, in reading images; in Music, teaching of musical notes, among others. The present study focuses on the acquisition of the Spanish language by high school brazilians students. Participated in the study six high school students from public school East Zone São Paulo, that attend classes at technical course of a particular network. Three studies containing repertoire initial evaluation, intervention and final repertoire evaluation were performed. The teaching took place in the collective context (researcher and participants) using a software. Study 1 aimed to teach reading and handwriting of the verb be in the present tense. The stimuli used were dictated verb (A), figure (B), printed verb (C). The AB, AC and AE relations were taught and tested relations selection (BC and CB), translation (CT and AT), oralization (BD and CD) and handwriting (AF). In Study 2, was taught to read and write handwritten words with J, LL or Ñ, corresponding with the definite article. Relations between dictated word (A), figure (B) and the written word (C) were also taught, being taught the AB, AC and AE relations and tested the BC and CB relations, (CT and AT) translation, oralization (BC and CD) and writing (AF and BE ) both words and sentence of generalization. Study 3 aimed to teach participants to give appropriate answers to the questions with Who is... / Who are... / How is/are... To do so, the participant is taught to relate print questions - Print Answer ( Qiri ), testing not taught relations (QiQt, QiRm, QiRo, QdQt, QdRm, QdRo, RiRt, QdQi e QdRi). The results showed that the teaching procedures based on equivalence stimulus model, enabled the emergence of behaviors not directly taught (the translation into Portuguese, reading, handwriting and name the verb to be , words and even of sentence in Spanish). In the latter study, it was observed that the teaching of a unique relation made the occurrence of Answering Questions with is... / Who are... / How is/are..., both orally and manuscript, and its translation into Portuguese